An investigation on the socio economic determinants for demand for technical and vocational training among the youth in Kajiado County, Kenya - Sankale, James; Sakwa, Maurice M.; Ndegwah, David J. (IPRJB)
Purpose: The study aimed at establishing the extent to which socio-economic background determines the demand in TVET among the youth in Kajiado County. Methodology: The study used a mixed method design of both qualitative and quantitative methods for the purposes of triangulation. Empirical figures of student enrolment were obtained using standardized formula, followed by in-depth interviews about their study habits and attitudes towards TVETs. Quantitative and qualitative forms of data was linked for three reasons: First, for confirming or corroborating each other via triangulation; second, for elaborating or developing analysis, providing richer details and third, for initiating new lines of thinking through attention to new ideas coming up, as well as and providing fresh insight (Rosmann and Wilson (quoted in Miles & Huberman, 1994). The study was confined to the natural settings and attempted to interpret phenomenon in terms of the meaning that people will bring as asserted by Denzin and Lincoln (2005). The study applied a descriptive cross- sectional survey as its quantitative research design. According to Cooper and Schindler (2003), the research design is appropriate if the study is concerned with finding out what, when, and how much of phenomena. Findings: From the research findings above, it can be inferred that socio economic background influence is key determinant of the demand for TVET courses. The study concludes that affordability of TVET programmes and the competition among household dependants for the acquisition of skills exerts influence on demand for TVET. Some parents nonetheless have challenges meeting the costs of TVET programmes. Given that the cost of TVET courses is uneven as some demand more resources than others; a parent’s income possibly determines the choice of the course for their children. If the income is low, the preference will be a cheaper course. This is further complicated by the high cost of living, especially in cases where the number of dependants in the family is high. This reduces some parents’ purchasing power to afford the TVET costs relative to their meagre income. Unique contribution to theory, practice and policy: Parents and students should build networks with members of the society who are of higher socio-economic status to enhance the ability of the graduates to gain opportunities in the labour market. The research can aid in advancing both the theoretical and practical knowledge and aims at getting the ‘best practice’ to act as a benchmark used in organizational problem solving. It therefore establishes a relationship between performance of youth polytechnics and the level of demand for TVET.
Keywords: youths; Investigate; determinant; demand; technical; vocational training; skills; poverty; socio-economic